„Informacja przetworzona” i „przetworzenie informacji” po nowelizacji ustawy o dostępie do informacji publicznej z 16.9.2011 r. - Sibiga, Grzegorz (Kwartalnik Prawa Publicznego, 2012)
Processing of information affects two rights: the right of access to public information and the right to re-use of public information. Since its beginning (1st January 2002), the Act on Access to Public Information has provided for the duty to disclose information only if it is particularly essential for the public interest. As a result of the amendments to the Act, enacted on 16th September 2011, the notion of processing of information was introduced in two articles, which, among other things, restricts the right to re-use. In the article the author explains the above notions taking into account Directive 2003/98/EC.